2015
DOI: 10.1186/s12906-015-0902-2
|View full text |Cite
|
Sign up to set email alerts
|

Chungsimyeonja-eum inhibits inflammatory responses in RAW 264.7 macrophages and HaCaT keratinocytes

Abstract: BackgroundChungsimyeonja-eum (CSYJE) is an herbal prescription used in traditional Oriental medicine for treating cerebral infarction by reducing ischemic damage. However, the effects of CSYJE on inflammation have not been verified scientifically.MethodsAnti-inflammatory effects of CSYJE was investigated to dertermine the inhibitory effects of CSYJE against inflammation using RAW 264.7 mouse macrophages and HaCaT human keratinocytes. To measure the effects of CSYJE on inflammatory mediators and cytokines/chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…HaCaT cells. The transcription factor STAT1 serves an important role in the regulation of skin inflammation and is associated with chemokine production in keratinocytes that have been treated with inflammatory stimuli (18,23). In the present study, TNF-α and IFN-γ stimulation notably increased the expression levels of p-STAT1 compared with the untreated HaCaT control cells (Fig.…”
Section: Effects Of Hss On the Activation Of Stat1 In Tnf-α-and Ifn-γsupporting
confidence: 53%
See 1 more Smart Citation
“…HaCaT cells. The transcription factor STAT1 serves an important role in the regulation of skin inflammation and is associated with chemokine production in keratinocytes that have been treated with inflammatory stimuli (18,23). In the present study, TNF-α and IFN-γ stimulation notably increased the expression levels of p-STAT1 compared with the untreated HaCaT control cells (Fig.…”
Section: Effects Of Hss On the Activation Of Stat1 In Tnf-α-and Ifn-γsupporting
confidence: 53%
“…Thus, it is necessary to develop anti-inflammatory drugs with improved efficacy against skin inflammation, with fewer side effects, that may be used over longer periods of time. Recently, various studies have reported on the inhibitory effects of traditional herbal formulas on skin inflammation (14)(15)(16)(17)(18) and have indicated that herbal formulas may be valuable alternative medicines for treating skin inflammation diseases. Hyangso-san (HSS) is a traditional herbal formula that has been used in Korea to treat symptoms of the common cold, including headache, pantalgia, fever and chills (19).…”
Section: Potential Inhibitory Effects Of the Traditional Herbal Prescmentioning
confidence: 99%
“…The membrane was washed three times with TBST at intervals of 10 min and developed using the SuperSignal West Femto Maximum Sensitivity Substrate (ultrasensitive enhanced chemiluminescent substrate) (NCI34095KR; Thermo Fisher Scientific Inc., Waltham, MA, USA). Subsequently, membranes were photographed and, densitometric band values were determined using the commercially available ChemiDoc XRS + Imaging System for quantitative analyses (Bio-Rad Laboratories) as described previously [16].…”
Section: Immunoblottingmentioning
confidence: 99%
“…In addition, tumor necrosis factor (TNF)-αincreases serum IgE levels, resulting in increased levels of inflammatory chemokines and cytokines. These inflammatory effects can be reversed by treatment with antiinflammatory candidates that inhibit signal transducer and activators of transcription (STAT) and nuclear factor (NF)-κB signaling pathways [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%